DOCTRINAL PROVISIONS OF THE GENERAL PROGRAM OF THE COMMUNIST PARTY OF CHINA AS A SYSTEM OF IDEATIONAL-THEORETICAL AND POLITICAL-IDEOLOGICAL PRESCRIPTIONS FOR RESEARCH OF MODERN CHINESE MARXISM - Vilkov, Viacheslav (Bulletin of Taras Shevchenko National University of Kyiv. Philosophy, 2022)
The article reveals ideological-theoretical, methodological, and politico-ideological basic principles for an adequate analysis of the specifics of modern Chinese (Sinicized) Marxism. The attributive features of modern Chinese Marxism (Marxism with Chinese specifics (the adaptation of Marxism to the Chinese Context, Sinicized Marxism), as the most effective version in world history for correcting and modernizing the axiomatics of the Marxist-Leninist theoretical model of social development, as well as improving the ideology of the ruling Communist Party in order to increase the effectiveness of its domestic and foreign state policies, have been characterized by means of concrete-historical and systematic comparative analysis of the ideational grounds and basic socio-philosophical postulates, political and ideological prescriptions of the program documents of the Communist Party of the Soviet Union and the Communist Party of China. Within the framework of this study, special attention has been paid to highlighting the essence and features of the Soviet and Chinese strategy of socialist construction, created to implement Marxist socialist and communist projects, as well as revealing the scientific evaluation of the differences between the political doctrines of the CPSU and the CPC in the interpretation of objective logic (the duration of stages, goals, and objectives of fundamental economic, social, political, and cultural transformations) of the process of constructing high-level development socialism ("developed socialism") and the further progressive movement of such a society to the phase of communism.